Instability in car-following behavior: new Nagel–Schreckenberg type cellular automata model. (7th August 2018) - Huang, Yong-Xian; Guo, Ning; Jiang, Rui; Hu, Mao-Bin
Abstract: In the past few decades, numerical models were proposed to study car-following behavior, in order to resolve the controversy about the fundamental relation between speed and spacing under various traffic conditions. Jiang et al (2014 Plos one 9 e94351, 2015 Transp. Res . B80 338–54) carried out a series of field experiments, revealing that the vehicle speed and its spacing span a 2D region in the speed-spacing plane and standard deviations of the velocities of cars fit to a concave curve. To describe this instability of car-following behavior, we proposed a new NaSch type model, in which a speed-dependent variable is introduced. The flow rate, spatiotemporal patterns and the velocity standard deviation can be in basic agreement with the experiment. Moreover, transitions of the traffic phases are reproduced and the fundamental relationship between flow rate, speed and density is presented.